Advanced theory of mind and children's prosocial lie-telling in middle childhood: A training study - Gao Q; Chen P; Huang Q; Wang Z (Elsevier Inc., 2024)
Children's advanced theory of mind (AToM) is concurrently associated with their prosocial lie-telling. However, the causal link between AToM and prosocial lie-telling has not yet been demonstrated. To address this gap, the current study adopted a training paradigm and investigated the role of AToM in children's prosocial lie-telling in middle childhood. A total of 66 9- and 10-year-old children who did not demonstrate any prosocial lie-telling in a disappointment gift paradigm at the baseline were recruited and randomly assigned to either the experimental group (n = 32) or an active control group (n = 34). The experimental group underwent a conversation-based training program of four sessions. The results showed significantly greater gains in AToM at the posttest for the experimental group children compared with the control group children, controlling for family socioeconomic status, children's literacy score, working memory, and inhibition. More important, the experimental group children were more likely to tell prosocial lies than the control group, even after controlling for the pretest AToM and other covariates. However, the training effects faded at the 6-month follow-up test after the training's completion. These findings provide the first evidence for the causal role of AToM in the development of prosocial lie-telling in middle childhood. The fade-out effect is discussed in the context of educational interventions.
Keywords: Advanced theory of mind; Conversation-based approach; Fade-out; Middle childhood; Prosocial lie-telling; Training; Humans; Child; Male; Female; Theory of Mind; Deception; Social Behavior; Child Behavior; Child Development